THE STATUS OF SPECIES DIVERSITY OF SEAWEEDS IN SURVEYED ISLANDS IN VIETNAM SEA - Duy, Do Anh; Khuong, Do Van (Vietnam Journal of Marine Science and Technology, 2014)
In 2010-2011, the project “Comprehensive surveys on biodiversity in coral reef ecosystems and islands in Vietnam sea aiming at the sustainable development” is carried out the assessment of the status of seaweed species composition at 19 islands in Vietnam sea region. By applying the morphological method and cells structure analysis, the authors have identified 376 species belonging to 62 families, 31 orders in 4 phyla of seaweed. Among them, there are 178 species of Rhodophytes, 94 Chlorophytes, 80 Ochrophytes (Phaeophytes) and  24 Cyanobacteriophytes. In studied areas, the highest quantity of species was revealed in Ly Son island with 125 species, following by Phu Quy -114 species, Phu Quoc -106 species etc. Ba Mun island has the lowest with 11 species only. From the total 376 species of seaweed there are 102 species are of economic importance, 5 species are rare and valuable that have been suffering extinction risk in Vietnam. These species should be protected, rehabilitated and developed. The species of seaweeds distribute mainly on the rocky bottom of tidal flats, on the contrary, the soft bottom has small number of seaweeds. The similarity index of seaweed species composition between studied areas were not high, the average is about 0.24.